Mitos da cultura africana: elementos de informação e preservação da memória na Comunidade Quilombola Alcantarense de Itamatatiua - Pereira, Cleyciane Cassia Moreira (2011)
The aim of this study is to examine the myths of African culture as elements of information in memory and preservation of the Community of Quilombola Alcantarense Itamatatiua. Consisting of specific objectives to identify, verify how the preservation, understanding of these myths, and the possibility of contribution to the continuation of studies and surveys that portray the history and memory black. The couple's Theory of the Imaginary by Gilbert Durand, we adopt the mitoanálise that allows simultaneous analysis of the myths with the methodology of qualitative ethnographic approach in order to describe, thick, the survey data collected through semi-structured direct observation and identification record. Explains the theoretical and methodological Theory durandiana with its functions, features and contributions to the historical course of humanity. Highlights concepts of information, memory and preservation addressed in CI. Points out the myths of African culture, the ancestry of black Alcantara and Maranhao in order to describe the socio-economic-political-cultural Itamatatiuenses. Identifies the mythological figures prevailing in African education, leisure and health from the lenses of the Basin and Semantic Topical Mimic. We conclude that the mythological information and its preservation should occur in partnership with the Law 10.639/03, and this information may bring back self-esteem and serve to perpetuate the tradition of the inhabitants of Itamatatiua.